Counteractive Effects of Copper Nanoparticles and Betacellulin on Ovarian Cells - Alexander V. Sirotkin; Paula Romero-Navarro; Barbora Loncová; Zuzana Fabová; Michaela Bartušová; Abdel Halim Harrath; Francisco Alonso (Nanomaterials)
Copper nanoparticles (CuNPs) are known to affect many ovarian cell functions. CuNPs, prepared using a chemical reduction method, were fully characterized by different means (TEM, DLS, XRD, Z potential, XPS, and AES). The resulting colloidal suspension contained needle-like CuNPs aggregates made of a core of metallic copper and an oxidized surface of Cu2O and CuO. The separate and coupled effects of CuNPs and the growth factor betacellulin (BTC) were analyzed on the control of some basic functions of ovarian cells. With this purpose, porcine ovarian granulosa cells, together with CuNPs, BTC, and both (CuNPs + BTC), were cultured. Viability and BrDU tests, quantitative immunocytochemistry, TUNEL, and ELISA were used to evaluate markers of the S-phase (PCNA) and G-phase (cyclin B1) of the cell cycle, cell proliferation (BrDU incorporation), cytoplasmic/mitochondrial apoptosis (bax) and extrinsic (nuclear DNA fragmentation) markers, and the release of estradiol and progesterone. CuNPs were accumulated within the cells and were found to reduce all the markers of proliferation, but promoted all the markers of apoptosis and the release of steroid hormones. When added alone, BTC raised the expression of all cell viability and proliferation markers, depleted the expression of all apoptosis markers, and stimulated the release of both estradiol and progesterone. Furthermore, BTC prevented and even reversed the effect of CuNPs on all the measured parameters, whereas CuNPs mitigated BTC’s effect on all the analyzed cell functions. These results support a direct toxic effect of CuNPs and a stimulatory effect of BTC on ovarian cell functions, as well as the capability of BTC to protect against the adverse effects of CuNPs.